ANALISIS KEPUASAN PASIEN PUSKESMAS MULTIWAHANA PALEMBANG - Musrifin Nasir (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
Clinics have been established in the entire country, to reach all areas of the health centerworks. They reinforced with supporting health center, and the Mobile Health Center. Unless it is forareas far from referral care facilities, health center equipped with inpatient facilities. Public HealthCentres should be able to quickly respond to the needs of society. Consequently Public HealthCentres requires human resources that have the expertise, skill. and capabilities that can improvehealth services to the community.Multiwahana Health Center Palembang has implemented theservices policies above but therealization of satisfaction achievement does not meet the expectations because there are stillcomplaints of patients with the services provided. From the results of data analysis and hypothesistesting , there are service Effect on patient Satisfaction. The value of the coefficient of multipledetermination (R2) is 62.5%